2017
DOI: 10.2298/gensr1702573m
|View full text |Cite
|
Sign up to set email alerts
|

Variability of morphological characters among ornamental sunflower collection

Abstract: The research describes the field comparison of 81 decorative sunflower genotypes. In order to assess genetic diversity of sunflower genotypes the studies were conducted in the field conditions during 2010-2015 at the Institute of Field and Crops, Novi Sad, Serbia. The genetic diversity of species Helianthus annuus L. has enabled the breeding work in the direction of the decorating and plant landscaping. Depending on the qualitative and quantitative characteristics, production of decorative sunflowers can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Six generations of selfing were carried out to insure the genetic purity of the developed genotypes. The genotypes were selected based on the flower characteristics and their single-stem properties (Mladenović et al 2017). The selected genotypes had a yellow, lemon, or orange colour of the ray flower.…”
Section: Methodsmentioning
confidence: 99%
“…Six generations of selfing were carried out to insure the genetic purity of the developed genotypes. The genotypes were selected based on the flower characteristics and their single-stem properties (Mladenović et al 2017). The selected genotypes had a yellow, lemon, or orange colour of the ray flower.…”
Section: Methodsmentioning
confidence: 99%
“…The only inbred line intended for bird feed, line 33, was in the separate group among the four conventional inbred and one HO line. Specific traits of inbred lines intended for different purposes are the presence of branching which frequently occurs in ornamental sunflower genotypes and white color of seed in the only inbred line intended for bird feed (LIN, 2005;MLADENOVIĆ et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The cultivated populations of E. fulgens in greenhouse showed a morphometric variation in vegetative structures, similar to the wild-growing groups, which suggests that these characteristics are highly stable in this species. In most studies of ornamental plants, phenotypic differences in structures with aesthetic or commercial value are evaluated; for instance, stem length, firmness, and flower number, size, colour, and odor in Peruvian lily [15]; branch number and length, flowering duration, height, disc and ligulate flowers, and central head diameter in sunflower [14]; and growth habit, ramification, foliar blade, and fruit shape, size, and colour in ornamental gourds to obtain ideal genotypes for cut flower, bouquets, arrangements, or pots [16]. Cultivation of E. fulgens in greenhouse demonstrated that it adapts and develops well under controlled conditions.…”
Section: Morphological Variation In Cultivated Populationsmentioning
confidence: 99%
“…To date, studies in which morphological variation has been evaluated between cultivated ornamental plants and their wild relatives are scarce worldwide [11,12]. Most research has focused on characterizing different genotypes of cultivated plants or with some level of handling [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%